Ground-state charge transfer in single-molecule junctions covalent organic frameworks for boosting photocatalytic hydrogen evolution - Rongchen Shen; Can Huang; Lei Hao; Guijie Liang; Peng Zhang; Qiang Yue; Xin Li (Nature Communications)
Abstract Ground-state charge transfer plays a vital role in improving the photocatalytic performance of D-A type covalent organic frameworks. However, limited studies have explored the modulation of photocatalytic performance in COFs-based photocatalysts through ground-state charge transfer. Here we show the formation of extremely intense ground-state charge transfer via a unique covalent bonding approach. We transform three-dimensional stacked COF-based S-scheme heterojunctions (FOOCOF-PDIU) into co-planar single-molecule junctions (FOOCOF-PDI). This co-planar single-molecule junction structure exhibits strong ground-state charge transfer compared to the traditional randomly stacked heterojunctions and individual COFs. Ground-state charge transfer induces charge redistribution and dipole moment formation, which enhances the built-in electric field intensity in single-molecule junctions. This enhanced built-in electric field promotes exciton dissociation and charge separation, resulting in improved photocatalytic efficiency. Therefore, a stable molecule-decorated COF with broad light absorption has been successfully obtained, whose hydrogen evolution rate can reach 265 mmol g−1 h−1. This work opens an avenue for exploiting photocatalytic mechanisms in COFs based on ground-state charge transfer effects.